Water Soluble Polymers - Alexander Penlidis (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This book on water soluble polymers (WSP) contains contributions that deal with this extremely popular area of scientific investigation in polymer science and engineering, both in academic and industrial environments. The book contents cover a wide variety of topics, starting from polymerization kinetics (emphasis on multicomponent systems), clarification of factor effects (for example, ionic strength, pH, monomer concentration, and how they influence important chain characteristics and properties), mathematical modelling, parameter estimation, and process design, and ending with applications (i.e., using the well characterized polymer molecules to deliver specific desirable properties for specific applications (hydrogels, cosmetics, drug release, flocculation, nanotechnology, enhanced oil recovery, polymer flooding, absorbents, crosslinking, and many others)). This book contains 17 very high quality contributions from author groups that span the globe and represent currently active researchers in the WSP area.